2020
DOI: 10.1097/jsm.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Head Acceleration Events Varies by Position and Play Type in North American Football

Abstract: Objective: The goal of this pilot study was to evaluate the number of head acceleration events (HAEs) based on position, play type, and starting stance. Design: Prospective cohort study. Setting: Postcollegiate skill development camp during practice sessions and 1 exhibition game. Participants: Seventy-eight male adult North American football athletes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
2
6
1
Order By: Relevance
“…30 For example, data from wearable head impact sensors obtained onfield can be used to ensure test methodologies are representative of actual loading conditions, to evaluate changes to rules of the game, and to identify drills and game scenarios that may be associated with a greater number of impacts or impacts of higher magnitude. 4,25,36 Currently, numerous, wearable head impact monitoring systems are available for use with varying form factors including impact sensors mounted in helmets, headbands, skin patches, earpieces, mouthguards, and retainers. 6,10,26,29,[31][32][33]40 These systems typically measure or estimate six-degree-of-freedom (6DOF) kinematics of the head during an impact which can be used to assess the severity of the impact and the likelihood of head injury.…”
Section: Introductionmentioning
confidence: 99%
“…30 For example, data from wearable head impact sensors obtained onfield can be used to ensure test methodologies are representative of actual loading conditions, to evaluate changes to rules of the game, and to identify drills and game scenarios that may be associated with a greater number of impacts or impacts of higher magnitude. 4,25,36 Currently, numerous, wearable head impact monitoring systems are available for use with varying form factors including impact sensors mounted in helmets, headbands, skin patches, earpieces, mouthguards, and retainers. 6,10,26,29,[31][32][33]40 These systems typically measure or estimate six-degree-of-freedom (6DOF) kinematics of the head during an impact which can be used to assess the severity of the impact and the likelihood of head injury.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, this study's results may not be generalizable to teams that follow American rules. Head impact frequency can vary within positional groups, 70 depending upon seniority and roster depth. 31 This study measured saccade latencies of all roster depths at different positions, including injured players who did not experience any head impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three male collegiate American football athletes (mean age = 21 2 years) participated in this study. The selected athletes were all seasoned starters who experience, and have experienced, a high frequency of HAEs throughout the athletic season (i.e., 16/23 athletes were non-speed linemen who sustain a high volume of impacts during practices and games) ( Lee et al., 2020 ; Lehman, 2013 ). Written informed consent was obtained from each participant in accordance with the Pennsylvania State University Institutional Review Board and in alignment with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Sensors were individually mounted on the inner surface, between the shell and padding, of each active player’s helmet prior to contact practice beginning. To avoid game disruption, no games were monitored; however, previous studies have revealed that most HAEs accumulate from practice sessions, not games ( Lee et al., 2020 ). Sensors were monitored throughout the season for integrity and functionality and outputs included peak translational acceleration (PTA; G-units) and impact location.…”
Section: Methodsmentioning
confidence: 99%